Evaluation of the cytotoxic and antimicrobial potential of epiphytic biomass obtained from Laminaria hyperborea biorefinery side-streams - Barouti, Angeliki; Herfindal, Lars; Vagolu, Siva Krishna; Homberset, Håvard; Tønjum, Tone; Kopplin, Georg; Jordheim, Monica (Frontiers in Marine Science, 2024)
Harvested Laminaria hyperborea contributes to approximately 3.3 million tonnes of epiphytes discarded as waste despite containing organisms such as red algae and bryozoa, known to produce a range of high-value and bioactive compounds. Our research aim is to valorize epiphyte biomass by exploring the cytotoxic and antimicrobial potential in various extracts and optimized fractionation by flash chromatography. All extracts and fractions were tested for cytotoxicity towards cell lines derived from Acute Myeloid Leukemia (AML), prostate cancer (PC-3), and breast cancer (MCF-7), as well as non-tumorigenic cell lines from the kidney and heart using metabolic activity as a read-out. Antimicrobial activity was assessed using microplate based Alamar Blue assay and minimum inhibitory concentration (MIC) to determine the MIC against various human pathogens. Six extracts demonstrated significant cytotoxicity across all five cell lines (EC50 values below 46 µg/mL), while hexane extract selectively targeted AML cells with EC50 of 1.1 µg/mL. The hexane and ethyl acetate extracts displayed antimycobacterial and antifungal activity (MIC 100 µg/mL). A multistep flash fractionation of the methanolic extract revealed several cytotoxic and antimicrobial activities. The flash fractions displayed a selective activity pattern depending on the elution solvent. Nine fractions were cytotoxic towards all cell lines (EC50 below 72 µg/mL), and four were highly cytotoxic (EC50 below 5.4 µg/mL). Two non-polar fractions were selective for the AML cell line. These results highlight the potential for discovering anticancer and antimicrobial compounds in epiphytes from Laminaria, necessitating further research on their active compounds. Overall, this work underscores the environmental and scientific value of converting marine by-products into a valuable resource, aligning with sustainability and ethical goals.